The Influence of Principal’s Leadership and Motivation on Teacher’s Performance (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims: (1) to determine and describe the influence of the principal’s leadership style on the performance of teachers; (2) to find out and describe the influence of leadership and motivation of school principals on the performance of teachers; and (3) to find out and describe the influence of the head’s leadership style and motivation on the performance of SMP Negeri teachers in Lempuing Jaya Sub-District, Ogan Komering Ilir Regency. This research was carried out at SMP Negeri 1, 2, 3, 4 Kematan with a total research sample of 100 teachers. Data collection techniques were carried out through observation, documentation studies, and distribution questionnaires. The validity test uses construct validity, while the reliability test uses Cronbach’s Alpha, Linearity Test and Normality Test. The results of this research show that there is a partially significant influence between leadership style and motivation on the performance of SMP Negeri teachers in Lempuing Jaya Sub-District, Ogan Komering Ilir Regency. There is a significant simultaneous influence between leadership style and motivation on the performance of Lempuing Jaya SMP Negeri teachers. This study contributes to give attention towards leadership style and motivation when the school will get good teacher’s performance.